Lack of Opsonic Antibody Responses to Invasive Infections With Streptococcus dysgalactiae - Bläckberg, Anna; de Neergaard, Therese; Frick, Inga-Maria; Nordenfelt, Pontus; Lood, Rolf; Rasmussen, Magnus (Frontiers in Microbiology, 2021)
Introduction Streptococcus dysgalactiae can cause severe recurrent infections. This study aimed to investigate antibody responses following S. dysgalactiae bacteraemia and possible development of protective immunity. Materials and Methods Patients with S. dysgalactiae bacteraemia in the county of Skåne between 2017-2018 were prospectively included. Acute and convalescent sera were obtained. All isolates were emm typed and ELISA was utilized to analyse specific antibody responses to bacteria and antigens. Bactericidal- and phagocytosis assays were applied to further establish antibody function. Results Sixteen patients with S. dysgalactiae bacteraemia were included of whom one had recurrent episodes of bacteraemia. Using ELISA with S. dysgalactiae isolates and mutants, development of IgG antibodies was demonstrated in few patients. Type-specific antibodies were demonstrated in one patient when recombinant M proteins as antigens, were applied. The type-specific serum mediated a small increase in phagocytosis but did not facilitate increased killing of the S. dysgalactiae isolate, carrying that M protein, in blood or by phagocytic cells. Conclusion S. dysgalactiae bacteraemia sometimes results in increased levels of antibodies to the infecting pathogen. We did not find evidence that these antibodies are effectively opsonizing. Apparent failure to produce opsonizing antibodies might partially explain why S. dysgalactiae can cause recurrent invasive infections in the same host.